Scheduling academic procession in UMP convocation ceremony using hill climbing - Nazreen Umeera, Dzulkifli (2019)
Academic assembly is one of the compulsory event in UMP Convocation Ceremony. Lecturers from all faculties in UMP will involve in the assembly. Since, there is limitation number of gown or hood, not all lecturers will be involved in the assembly. This thesis will differentiate three techniques that can be applied for scheduling Academic assembly in UMP Convocation Ceremony. A prototype will be develop based on the proposed algorithm. This thesis also provides the implementation process of the prototype and the proposed algorithm. The result that produced by the prototype will be compared with the old schedule.